Using HAADF-STEM for atomic-scale evaluation of incorporation of antibacterial Ag atoms in a β-tricalcium phosphate structure. Issue 31 (5th August 2020) - Gokcekaya, Ozkan; Ueda, Kyosuke; Narushima, Takayuki; Nakano, Takayoshi
Abstract : HAADF-STEM technique is introduced to locate the incorporated antibacterial Ag atoms in beam-sensitive β-TCP structure. Abstract : Structural evaluation of ionic additions in calcium phosphates that enhance their performance is a long-lasting area of research in the field of biomedical materials. Ionic incorporation in β-tricalcium phosphate (β-TCP) structures is indispensable for obtaining desirable properties for specific functions and applications. Owing to its complex structure and beam-sensitive nature, determining the extent of ion incorporation and its corresponding location in the β-TCP structure is challenging. Further, very few experimental studies have been able to estimate the location of Ag atoms incorporated in a β-TCP structure while considering the associated changes in lattice parameters. Although the incorporation alters the lattice parameters, the alteration is not significant enough for estimating the location of the incorporated Ag atoms. Here, Ag incorporation in a β-TCP structure was evaluated on atomic scale using scanning transmission electron microscopy (STEM). To the best of our knowledge, this is the first report to unambiguously determine the location of the incorporated Ag atoms in the β-TCP structure by comparing z -contrast profiles of the Ag and Ca atoms by combining the state-of-art STEM observations and STEM image simulations. The Ag incorporation in the Ca(4) sites of β-TCP, as estimated by the Rietveld refinement, was in good agreement with the high-angle annular dark-field STEM observations and the simulations of the location of Ag atoms for [001] and [010] zone axes.